2004
DOI: 10.1088/0953-8984/16/39/013
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of bipyridine molecules on Au(110) as measured by reflection anisotropy spectroscopy

Abstract: The reflection anisotropy spectra of 2,2 -bipyridine and 4,4 -bipyridine adsorbed onto an Au(110) surface in an electrochemical cell demonstrate that both systems form ordered structures. It is shown that reflection anisotropy spectroscopy can be used to distinguish between structural isomers adsorbed on the Au(110) surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…5,6 In this work we present the results of studies of adenine adsorbed at Au͑110͒/electrolyte interfaces using reflection anisotropy spectroscopy ͑RAS͒, which is a surface sensitive optical technique that can provide information on the orientation of molecules adsorbed at interfaces. [7][8][9][10][11][12][13][14][15][16][17][18][19] Initial studies of adenine adsorbing onto mercury electrodes showed that the adenine molecule undergoes a phase transition from planar to vertical as the potential is changed. 20,21 There have been a number of electrochemical studies of the adsorption of adenine on the Au͑111͒ and Au͑100͒ surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In this work we present the results of studies of adenine adsorbed at Au͑110͒/electrolyte interfaces using reflection anisotropy spectroscopy ͑RAS͒, which is a surface sensitive optical technique that can provide information on the orientation of molecules adsorbed at interfaces. [7][8][9][10][11][12][13][14][15][16][17][18][19] Initial studies of adenine adsorbing onto mercury electrodes showed that the adenine molecule undergoes a phase transition from planar to vertical as the potential is changed. 20,21 There have been a number of electrochemical studies of the adsorption of adenine on the Au͑111͒ and Au͑100͒ surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The optical technique of RAS has considerable potential for the study of interactions between important biological molecules and surfaces . It is one of the few surface science techniques able to bridge the gap between the UHV and ambient environments, and the technique has been shown to provide information on the orientation of adsorbed molecules. Recent studies have shown that RAS can yield insight into the metal/liquid interface and to the interactions between molecules in solution and metal surfaces. , …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Recent studies have shown that RAS can yield insight into the metal/liquid interface [8][9][10][11] and to the interactions between molecules in solution and metal surfaces. 12,13 The strategy is to determine the differences between the RAS of the adsorbed molecules and the clean Au(110) surface as a function of the applied voltage and to compare these differences for the three amino acids, cysteine, cystine, and methionine, in order to gain insight into their binding modes by exploiting the different coordination of the S groups in the three molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of ∆n = (n 1 -n 2 ) can be estimated from the stress birefringence coefficient. Assuming n 1 is the refractive index of PDMS at 635 nm [26] and a birefringence coefficient of 13.5 x 10 -5 (MPa -1 ) then using equation (15) ∆R/R is in the range 0 -5 x 10 -3 for the range of extensions in figure 3. In this estimation any dispersion in n 1 has been ignored;…”
Section: Discussionmentioning
confidence: 99%